Transplantation reported by a newspaper - Pavani, Priscila; Nunes, Wilma Aparecida; Melicardi, Cristiane Aparecida (Brazilian Journal of Transplantation, 2007)
Organ transplant as therapy has been benefited from scientific advancements, providing a better quality of life to the receptor, reducing donor complications, and even reaching an efficiency degree that attains a null or almost null mortality rate. This is an innovatory and well spread treatment modality that involves ethical, moral, religious, cultural, and legal aspects which establishes some barriers for its practice in an effective way. Purpose: The purpose of this study was to verify the content of information published by the newspaper “Folha de São Paulo” approaching the subject “transplants”. Methods: The methodology used was the documental retrospective research of online publications using the word “transplant” as searched term; the period evaluated was from 1994 to 2005. Results: As result, 2,134 newspaper’s articles were selected — the “daily” editorial that presented a higher amount of articles and the most spread subjects were those related to the findings, the single queue and the legislation, evidencing a clear concern on the text of the law, which was improved along the years. Conclusion: The dilemmas posed by an overcharged health system to cope with the demand and which deals with great difficulties to attain an internal organization to meet the population’s needs of a country of continental dimensions are disclosed, where islands of excellence emerge; however, a major part of potential persons who could benefit themselves from such therapy is left aside. Added to this, it is clear the impact of the media on the values of a people still in need of more education and information to assume its citizenship and claim their rights.